Superconductivity with and without glue and the role of the double-occupancy forbidding constraint in the t-J-V model - Zinni, Luciano Sebastian (2021)
The occurrence of retarded (with glue) and unretarded (without glue) pairing is thoroughly discussed in cuprates. We analyze some aspects of this problem in the context of the t − J − V model in a large- N approximation. When 1 / N renormalizations are neglected the mean-field result is recovered, where the unretarded d -wave superconducting pairing triggered by the spin-exchange interaction J is obtained. However, the presence of a nonnegligible nearest-neighbors Coulomb interaction V ( q ) kills superconductivity. If the non-double-occupancy constraint and its fluctuations are considered, the situation changes drastically. In this case, V ( q ) is screened making d -wave superconductivity very robust. In addition, we show that the early proposal for the presence of an unretarded pairing contribution triggered by the spin-exchange interaction J can be discussed in this context.